Decreased total antioxidant response and increased oxidative stress in Behcet's disease - Isik, Ahmet; Koca, Suleynian Serdar; Ustundag, Bilal; Selek, Sahabettin (Tohoku Univ Medical Press, 2007)
Behcet's disease (BD) is a chronic systemic inflammatory disease. Inflammatory reactions trigger the oxidative stress and oxidants decrease the level of antioxidants. In the present study, we aimed to determine serum oxidative/antioxidative status in patients with BD. Serum antioxidative status was evaluated by measuring total antioxidant capacity (TAC), paraoxonase 1, arylesterase, sulfhydryl groups and ceruloplasmin in patients with BD and in healthy controls. Serum oxidative status was evaluated by measuring total peroxide (TP), lipid hydroperoxides and oxidative stress index (OSI). OSI was calculated by percent ratio of TP to TAC. Serum levels of TAC, sulfhydryl groups and activities of paraoxonase 1, arylesterase, and ceruloplasmin were significantly lower in patients than in controls (p < 0.001 for all). In contrast, TP, lipid hydroperoxides and OSI values were significantly higher in patients than in controls (p < 0.001 for all). Further, the level of TAC was negatively correlated with the levels of TP, lipid hydroperoxides and OSI both in the 131) (r = -0.578, p < 0.01; r = -0.559, p < 0.01 and r = -0.552, p < 0.01, respectively) and the control groups (r = -0.469, p < 0.05; r = -0.351, p < 0.05 and r = -0.391, p < 0.05, respectively). These results indicate that the oxidant parameters increased and antioxidant parameters decreased in patients with BD; therefore, these patients might have been exposed to oxidative stress. We suggest that impaired oxidant/ antioxidant balance should be taken into consideration in the follow-up of patients with BD.
Keywords: Behcet's disease; total antioxidant response